Multimedia based Computer Aided Learning (CAL) system for Geografy and Kajian Tempatan - Baharom, Fauziah; Abdul Rahim, Rahela; Muhd Darus, Norida; Marzuki @ Mat, Zaharin; Shiratuddin, Norshuhada (1998)
The invention of cheap and powerful machines has brought the era of the electronic classroom one step nearer.Every where in the world; schools, colleges and universities teachers of all subjects are using computers to enhance and assist the process of learning and teaching.It is usually in areas where other media are less effective that computer based material is justified. Therefore, it is important to bring computers into the classroom rather than to keep them in an inner sanctum.Students always find computing very exciting and they tend to learn explore the machines at a greater.